Incorrect use for Inhalation Techniques of Inhaled Medication among Children with Asthma in Qassim Region: Prevalence and its Risk - Aisha Almutairi, Abdullah M. Alolayan, Afrah H. Alazmi, Raghad Y. Alghurayr, Rehab A. Alrashidi, Jolan S. Alsaud, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Asthma is one of the world's most common chronic respiratory disorders, and inhalers are frequently recommended to help manage allergy symptoms, improve quality of life, and reduce the risk of exacerbations or flare-ups. In Saudi Arabia, the prevalence of asthma is relatively high. Inhaler misuse can result in a variety of problems. This study aims to measure the prevalence of correct use of inhalation techniques of inhaled medication among children with asthma and investigate whether improper inhaler use can lead to uncontrolled bronchial asthma and its problems. Material and Methods: A cross-sectional study used a validated self-administered Arabic questionnaire given to 180 participants who visit paediatrics pulmonology clinic at Qassim University Medical City and Dr. Sulaiman Alhabib Hospital in Buraydah from June to December 2021. This study used a completed questionnaire consisting of sociodemographic characteristics, questions assess the participants’ condition and its severity, and questions to evaluate their inhalation technique of inhaled medication and if they were educated about the correct inhalation technique or not. Results and Conclusion: Findings demonstrate that number of ED visits is significantly associated with the time of diagnosis and frequency of using an inhaler (P=0.032) and (P=0.010) respectively. When we looked at the relationship between several characteristics and the timing of diagnosis, we discovered that age and times of using an asthma inhaler (Ventolin) in one week were significantly related (P=0.000). Revealing association between variables and frequency of using inhaler; the significant association with the source of advice about on the correct use of inhaler (P=0.005), and way of fixing the mask (P=0.040). Although our study showed enhanced knowledge and techniques using inhalers, physicians and other health workers should teach children and their caregivers how to use their inhalation devices properly whenever possible, and rectify errors when they occur, to ensure that medication is delivered effectively. As a result, future awareness campaigns should focus more resources on educating families and caregivers of asthmatics on correct medication use to avoid asthma complications and control asthma episodes for children.